Triage of Conservation Needs: The Juxtaposition of Conflict Mitigation and Connectivity Considerations in Heterogeneous, Human-Dominated Landscapes - Goswami, Varun R.; Vasudev, Divya (Frontiers in Ecology and Evolution, 2017)
Conservation of wide-ranging endangered species is increasingly focused on large heterogeneous landscapes. At such scales, particularly when conservation landscapes are human dominated, it is imperative that prioritization techniques be used to allocate limited resources wisely. Moreover, spatial aspects of conservation planning warrant key consideration within these landscapes, such that certain sites that are key to either mitigating threats to species or to maintaining ecological processes, are prioritized. However, there are often multiple conservation needs, and multiple associated constraints, for species conservation in such landscapes. While there are tools to prioritize sites based on single or few conservation requirements and constraints, there is less knowledge on how these conservation needs, or corresponding management interventions, relate to each other in a scenario where conservation focus on one issue potentially detracts from another. We take the specific example of two conservation needs that are central to landscape-scale conservation of the endangered Asian elephant Elephas maximus, namely the maintenance of connectivity, and the mitigation of human–elephant conflict. We show that conservation decision making, in addition to considering which species and sites to focus on, should also prioritize conservation needs. We review documentation of conflict mitigation and examine if the maintenance of connectivity was simultaneously addressed, and if so, whether optimal conservation solutions differed when connectivity considerations were included. We conclude with a discussion on the triage of conservation needs, and future prospects and challenges in ensuring that landscape-scale conservation strategies accounts for multiple interacting conservation needs for endangered species in heterogeneous human-dominated landscapes.